Myanmar : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in Myanmar during 1992-96. There has been a strong recovery in output in response to reforms, with annual economic growth averaging about 8 percent during 1992/93-1995/96. The recovery has been driven by an increase in agricultural production and foreign investment, especially in tourism and extractive industries. Official estimates suggest that the economy grew by 9.8 percent in 1995/96. During 1992/93-1995/96, annual agricultural output rose by an average of about 8 percent per year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet